Determinants of Anemia in Teenage Girls Madrasah Aliyah Negeri - Een Husanah; Widya Juliarti (Institute of Computer Science (IOCS), 2021)
Anemia is a state of decreased hemoglobin, hematocrit and red blood cell counts below normal values. Anemia occurs as a result of a deficiency of one or several essential food elements that can affect the emergence of these deficiencies. Around 54% of adolescent girls in the world experience anemia, while in Indonesia the prevalence of anemia in adolescent girls in 2015 was 28%. Data from the Madrasah Aliyah Public Health Center of Tembilahan Hulu in 2017 were 59 incidents. The purpose of the study was to determine the factors related to the incidence of anemia among adolescent girls in Madrasah Aliyah Negeri Tembilahan Hulu in 2019. The research method was quantitative analytic with a cross sectional research design. The respondents were all female adolescent students in grades X and XI, the study was conducted in July 2019 The sample in this study were all teenage girls students in grades X and XI totaling 82 respondents. The sampling technique was random sampling with the proportional sampling method. The analysis used is univariate and bivariate analysis with Chi-Square test, the measuring instrument used is a questionnaire and computerized data processing (SPSS). The results showed that there was a relationship between eating habits (p value 0.010), POR value = 3.638 (1.455-9.095), nutritional status (p value 0.009), POR value = 3.692 (1.477-9.231), menstrual pattern (p value 0.000), POR value = 20,667 (6.615-64,566), knowledge (p value 0.021), POR value = 3,235 (1,284-8,154). It is recommended to health workers, especially the Tembilahan Hulu Public Health Center, to check and give Fe tablets more often to adolescents at Madrasah Aliyah Negeri Tembilahan Hulu and provide information and socialize about anemia so that Madrasah Aliyah Negeri schools make more efforts to improve health.